Accession in Centella asiatica; Current Understanding and Future Knowledge - Gbolahan, Balogun Wasiu; Abiola, Adebayo Ismail; Kamaldin, Jahangir; Ahmad, Mohammad Ayaz; Atanassova, Maria S. (Oriental Scientific Pub Co, 2016)
Centella asiatica is described as a potential cure-all because of its wide usage. The accessions in Centella asiatica make standardisation important before using it. In Malaysia alone, there are more than 15 accessions of Centella asiatica with each having variation in their secondary metabolites. There are several reports from India to Korea, from Madagascar to Malaysia and from Thailand to South Africa about variations in chemical profiling of secondary metabolites and the reasons for these variations in Centella asiatica. Despite all these reports, there has been no attempt to bring all these variations together and discuss them under one heading resulting into scattered information about accession in Centella asiatica. In this review, we discuss the impact of accessions in Centella asiatica and what more need to be done to our knowledge of accession in Centella asiatica.